Studi Struktur Mikro dan Jenis Mineral Batuan Mata Air Panas menggunakan SEM-EDX dan FTIR di Kelurahan Woloan Satu Utara Kota Tomohon - Geraldi Saputera Kapoh; Donny Royke Wenas; Alfrie Musa Rampengan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
Volcanoes around area there are usually geothermal manifestations, one of which is the hot springs manifestations in North Woloan Satu Tomohon City. The purpose of this study was to determine the microstructure and elemental composition of rocks as well as the types of rock minerals in the manifestation of hot springs in Woloan Satu Utara, Tomohon City, North Sulawesi Province. The research was carried out by analyzing the rock samples using SEM-EDX and FTIR. The results showed that the elemental composition of the rock 1 is O, Si, and Al with content percentage O 35,76%, Si 58,57%, and Al 5,67% and elemental composition of the rock 2 is O and Si with content percentage O 47,68% and Si 52,32%. From the results of FTIR characterization, for the rock 1 were obtained mineral types is Quartz (SiO2) and Kaolinite (2H2O Al2O3 2SiO2). And for the rock 2 were obtained mineral types is Quartz.